EIB Working Paper 2020/05 - Financing constraints and employers' investment in training (Volume 2020/5) - Weiss, Christoph (European Investment Bank, 2020)
Using a representative sample of European firms, this paper studies whether and to what extent financing constraints affect employers' decisions to invest in employee training. It combines survey data on investment activities with administrative data on financial statements to develop an index of financing constraints. It estimates that a 10 percent increase in this index reduces investment in training as a share of fixed assets by 2.9 to 4.5 percent and investment in training per employee by 1.8 to 2.5 percent. The paper documents that lower investment in training reduces productivity, and show that firms facing tighter financing constraints cut back the investment in training and tangible assets less than investment in R&D and software and data.